Analysis Of The Use Of Social Media And Brand Image In Influencing Purchasing Decisions: The Role Of Consumer Review Intervention - Santi Maria; Cucu Hodijah; Santo Dewatmoko (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study examines the intricate dynamics of the Use of Social Media (USM), Brand Image (BI), Consumer Reviews (CR), and Purchasing Decisions (PD) within the context of PT Silga Perkasa. Through a path analysis, we investigate both direct and indirect effects to understand the relationships between these variables. The results indicate a significant positive relationship between social media usage and consumer reviews, with subsequent impacts on purchasing decisions. Additionally, a direct and significant link is observed between brand image and purchasing decisions. However, the mediation role of consumer reviews between brand image and purchasing decisions is found to be non-significant in this specific setting. These findings provide valuable insights for businesses, emphasizing the strategic importance of leveraging social media for positive consumer reviews and the direct influence of a positive brand image on purchasing decisions.